LEGAL BOUNDARIES OF THE USE OF ELECTRONIC MEANS OF TRACKING ACTIVITY PROBATION CRIMINAL EXECUTIVE INSPECTION - Baranov Максим Николаевич; Zhumzhaeva Айдана Еркиновна (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2013)
The article deals with the legislative boundaries of the use of electronic means of tracking the activities of probation criminal executive inspection.